A Case Study on the Impact of Organizational Citizenship Behavior on Total Quality Management in an Indian Public Sector Electrical Manufacturing Subsidiary - Faizal, Mohammed; Mathew, Asish O; M. J, James (Journal of Asian Business Strategy, 2015)
Since 1970s, the study on Organizational Citizenship Behaviour (OCB) has been conducted and the importance of this extra-role behaviour has been established. This study is conducted with a purpose of examining the impact of OCB on Total Quality Management (TQM), and to single out the most influential element of OCB towards TQM. The study was conducted in a public sector electrical machine manufacturing company that is located in South India. The data was collected using a questionnaire and Structural Equation Modeling (SEM) using Partial Least Square (PLS) method was employed to analyse the data and test the hypotheses. The results of the research shows the influence of each of the five dimensions of OCB viz. altruism, courtesy, dedication, sportsmanship and civic virtue on TQM, and explains the influence of Organizational Citizenship Behaviour dimensions on Total Quality Management in the context of an electrical manufacturing company. The study highlights the dimensions of OCB that significantly influence the Total Quality Management, and suggestions are provided to help the stake holders in strategic planning.